Uji Formulasi Pupuk Hayati Cair dengan Penambahan Bacillus Cereus terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea Mays Saccharata Sturt.) - Hapsoh, Hapsoh; Dani, Isna Rahma; Rahman, Abdul (Universitas Medan Area, 2021)
This study aims to determine the effect of giving several liquid biological fertilizer formulations with the addition of B. cereus and get the best formulation to increase the growth and yield of sweet corn. The field experiment was conducted in the Faculty of Agriculture experiment station, Riau University located in Pekanbaru from July 2018 to October 2018. The research was carried out experimentally using a completely randomized design consisting of five treatments with four replications. The treatments tested were P1: B. cereus without formulation, P2: 100 ml B. cereus + 1 l wastewater of rice + 1 g chitin + 100 ml molasses, P3: 100 ml B. cereus + 1 l wastewater coconut + 1 g chitin + 100 ml molasses, P4: 100 ml B. cereus + 1 l tofu liquid waste + 1 g chitin + 100 ml molases, P5: 100 ml B. cereus + 1 l palm oil mill effluent + 1 g Chitin + 100 ml molasses. The parameters observed were plant height, age of female flower emergence, harvest age, stem diameter, weight of cob with cornhusk, weight of cob without cornhusk, length of cob without cornhusk, diameter of cob without cornhusk, number of rows of corn kernels. The results showed that all treatments have not been able to improve the growth response and yield of corn plants and all formulations of B. cereus biological fertilizer tested have not found the best formulation.